Development and validation of the organizational stressor indicator for sport performers (OSI-SP) - Arnold, R.; Fletcher, D.; Daniels, K. (Journal of Sport & Exercise Psychology, 2013)
The series of related studies reported here describe the development and validation of the Organizational Stressor Indicator for Sport Performers (OSI-SP). In Study 1, an expert and usability panel examined the content validity and applicability of an initial item pool. The resultant 96 items were analyzed with exploratory factor analyses in Study 2, with the factorial structure comprising 5 factors (viz., Goals and Development, Logistics and Operations, Team and Culture, Coaching, Selection) and 33 items. Using confirmatory factor analyses, Studies 3 and 4 found support for the 5-factor structure. Study 4 also provided evidence for the OSI-SP`s concurrent validity and invariance across different groups. The OSI-SP is proposed as a valid and reliable measure of the organizational stressors encountered by sport performers.